Lectotypification of Brazilian species of Vitex Tour. ex L. (Lamiaceae) - França, Flávio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2010)
Lectotypes are designated for the following taxa of Vitex Tour. ex L. (Lamiaceae) from Brazil: Vitex brevilabiata Ducke, V. duckei Huber, V. gardneriana Schauer, V. schaueriana Moldenke, V. triflora Vahl var. angustiloba Huber, V. triflora var. kraatzii Huber and V. triflora var. tenuiflora Huber.